1993
DOI: 10.1136/jmg.30.3.189
|View full text |Cite
|
Sign up to set email alerts
|

A study of DNA methylation in myotonic dystrophy.

Abstract: We have examined the hypothesis that the severe congenital form of myotonic dystrophy is caused by genomic imprinting at the level of differential DNA methylation of maternal and paternal alleles. Probes encompassing the 5', central, and 3' regions of the myotonic dystrophy protein kinase gene were used on blots of blood DNA from congenital and adult onset patients, digested with combinations of methylation sensitive and insensitive restriction enzymes. We observed similar patterns of methylation in each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
7
25
2
Order By: Relevance
“…Both DM1 fetus and adult samples were not methylated downstream of the TNR [85]. Earlier reports show conflicting data, but these studies used small sample cohorts and different tissues [86][87][88]. It is clear, however, that differential DNA methylation in regions flanking the TNR in DMPK, particularly in different tissues, is likely to be an important contributing factor to the variable clinical outcome of this disease.…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 79%
“…Both DM1 fetus and adult samples were not methylated downstream of the TNR [85]. Earlier reports show conflicting data, but these studies used small sample cohorts and different tissues [86][87][88]. It is clear, however, that differential DNA methylation in regions flanking the TNR in DMPK, particularly in different tissues, is likely to be an important contributing factor to the variable clinical outcome of this disease.…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 79%
“…It was shown that CTG repeats affect chromatin structure [31], but it seems that the repeat does not affect DMPK transcription, because mutant transcripts were detected by reverse transcription-polymerase chain reaction and Northern analysis [30]. Some studies demonstrated that a DNA region containing long CTG repeats could be hypermethylated [32], affecting transcription in the region of CTG repeats, but others found no effect of CTG repeats on DNA methylation [33]. Several reports described abnormalities in DMPK RNA processing.…”
Section: Two Distinct Mechanisms For Dm Mediated By Rna-binding Protementioning
confidence: 95%
“…The (CTG),, repeat might also cause changes in methylation status within the region. One study failed to detect such changes between normal and DM material, but the analysis was not comprehensive [23]. Congenitally affected muscle, kidney and pancreas show delay in maturation [24,25], and it is possible that expression of DMAHP plays a particular role in early development of these tissues (DMAHP has already been shown to be expressed in them [17]).…”
Section: Exonamentioning
confidence: 98%